Analisis Sistem Pengendalian Intern Dalam Kaitannya Dengan Keamananharta Perusahaan Pada CV. Kencana Jaya Di Bandar Lampung (Study Kasus pada CV. Kencana Jaya di Bandar Lampung) - Habiburrahman HABIBURRAHMAN; Ayu Widia Ningrum; Riswan RISWAN (Jurnal Akuntansi dan Keuangan, 2012)
Success or failure of the companys management is generally characterized by the ability of management to control the operational activities of the company, so that its implementation in accordance with a predetermined plan.With a good system of internal control, it is expected that the implementation of the operational activities of the company in accordance with existing plans and actions to minimize the harm to the company, so that the goal can be achieved by well planned. The problem with the CV. KENCANA JAYA is increasing doubtful receivables (loss) for 4 (four) periods, while the issue is whether a good internal control system can reduce the risk of CV company property. Kencana Jaya. The purpose of research is to determine how good internal control when connected with the implementation of the internal control system on sales and cash receipts on the CV. Kencana Jaya Bandar Lampung. While the information and consideration in decision making.Data collection methods used, the study of literature and field research while the method of analysis is qualitative analysis. From the results of evaluation of the system of internal control over sales and cash receipts, it can be concluded, that the system of internal control over sales has occurred geminating lending function, order by phone often does not proceed with the purchase order entry, and not proceed with the purchase order entry, and do not miss out any checks before approving loan collection. For it should be held separate sales function with the function of providing credit, also orders must be based on the purchase order, and prior to providing credit approval forged check gets first collection. While the system of internal control over accounts receivable, the company did not make the list and not sending receivable aging statement subscriptions receivable. For the company should make a list of accounts receivable aging and send a statement to the subscription receivable. While the system of internal control over cash, the company did not conduct a physical inspection of cash with a note, either periodic or sudden. Not a list of details receiving money, and physical cash / checks are not kept in a safe place (safe). Therefore the company should always perform a physical examination with a cash account, whether periodical or sudden, make a list of the details of the receipt of money, and keep physical money / checks in a safe place (safe).